Pretravelling Health-Seeking Behavior, Knowledge of Vaccines, and Attitudes Toward Travel Health among Malaysian Travelers - Zulkhairul Naim Sidek Ahmad; Khairul Anwar Zarkasi; Nur Zuliani Ramli; Farrah Ilyani Che Jamaludin; Muhammad Kamil Che Hasan (Wolters Kluwer, 2022)
Background: Travelers are at higher risk of developing health‑related problems, especially travel‑related diseases, and this remains a major public health burden. Aims: To assess pretravel health behavior‑seeking factors, knowledge of vaccine, and travel health attitudes. A cross‑sectional design among Malaysian travelers. Methods: An online survey was conducted from December 2017 till March 2018 among 226 participants. Demographic data, pretraveling health behaviors, knowledge of vaccine‑preventable diseases, and travel health were asked. Independent t‑test and ANOVA were performed using SPSS version 20. Results: Among travelers, 51.3% and 63.7% used health‑related information on their destination before departure and collected information on possible travel hazards at their destination. Participant age (P = 0.02), monthly income (P = 0.01), predeparture health information (P = 0.03), information on possible hazards (P = 0.04), and travel health advice from medical professionals (P = 0.03) have been reported as a major predictor of knowledge of vaccine‑preventable disease. Travelers’ gender (P = 0.01), household income (P = 0.01), and travel health advice from professionals (P = 0.002) were significantly associated with travel health attitude. Conclusions: Sociodemographic and pretravel health‑seeking behavior influence knowledge of vaccine‑preventable disease and attitudes towards travel health which requires a public health need for community outreach programs targeting this group.